STRUCTURAL AND PHASE TRANSFORMATIONS IN CONDENSED SELENIUM - Minaev, V S; Timoshenkov, S P; Kalugin, V V (Journal of Optoelectronics and Advanced Materials, 2005)
At normal pressure selenium exists in several forms of condensed state: crystalline (hexagonal Sen, a-, beta-, y-monoclinic Se8, monoclinic Se8), rhombohedral Se6, a- and beta-cubic Se, amorphous Se (red, brown and black Se), 4 liquid modifications, vitreous selenium. Structural and phase transformations taking place at heating as well as at cooling (or at constant temperature) of all above indicated selenium forms have been considered. The analysis of transformations inside of different Se forms and between them has been made on the base of the concept of the polymeric-polymorphoid structure of glass and glass-forming liquid using data of diffractometry, IR-, Raman- and UV-photoelectron spectroscopy as well as results of heat capacity alterations in the range of Se glass transition and enthalpy of transformation of non-crystalline Se forms into others.